The Remote Control of Fertility: Evidence from the Transition to Digital Terrestrial Television in Italy - Andrea Caria (CESifo GmbH, 2024)
This study investigates the causal impact of Italy's transition from analog to digital terrestrial television on fertility rates, exploiting the staggered rollout between 2008 and 2012 as a natural experiment. Employing a difference-in-differences analysis and a doubly robust estimator, I find a statistically significant negative effect of digital terrestrial television adoption on fertility, particularly pronounced in urban, progressive areas characterized by low pre-treatment fertility, fewer young couples with children, higher population density, and taxpayers. While a simple time substitution effect (between television viewing and reproductive activities) is unlikely to be the primary driver, evidence suggests that digital terrestrial television facilitated more individualized viewing experiences through increased household television ownership. The findings point to a significant shift in gender roles following digital terrestrial television adoption: I observe an increase in female labor force participation and a more equitable division of domestic work, with men undertaking a larger share of lighter household tasks.
Keywords: J13; J16; L82; C23; D83; 330; reproductive decisions; digital terrestrial television; media influence; difference-in-differences analysis